Policy of Islamic Family Law in Textual and Historical Approach - Jayus, Muhammad; Karimah, Siti; Yudha, Gesit; Irham, M.; Latifah, Arif (KnE Social Sciences, 2024)
The policy of family law in Indonesia is based on principles stipulated in the Civil Code (Kitab Undang-Undang Hukum Perdata or KUHPerdata) and several other laws that regulate marriage, divorce, children’s rights, and joint property in marriage. In formulating policies, a classic approach has been traditionally used. This research employs a library method, which involves collecting relevant texts and manuscripts for analysis and conclusions. The following are some important family law policies in Indonesia: marriage, divorce, children’s rights, and joint property in marriage. Fiqh not only faces difficulties in resolving various social problems and issues but also struggles in defining itself, particularly in the context of formulating legal methods to address these problems. As an initial step toward reconstructing fiqh, this article attempts to propose a solution in fiqh methodology, namely a unified approach to Shari’ah and social inference. In essence, this method aims to bridge and “integrate” the textual (normative) and contextual (historical-empirical) approaches simultaneously within an “Islamic” scientific research model. The offered conclusion is that both textual and historical approaches are crucial in formulating policies of Islamic family law. Keywords: policy, Islamic family law, approach